2019
DOI: 10.1093/biolre/ioz114
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 1 is a new biomarker of human oocyte competence: expression and hormonal regulation throughout late folliculogenesis

Abstract: Context Prokineticin 1 (PROK1) quantification in global follicular fluid (FF) has been recently reported as a predictive biomarker of in vitro fertilization (IVF) outcome. It is now necessary to evaluate its clinical usefulness in individual follicles. Objectives To evaluate the clinical value of PROK1 secretion in individual FF to predict oocyte competence. To determine the impact of follicular size, oocyte maturity, and gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…According to Canosa, et al, reduced levels of Cx43 expression in the cumulus cells, coupled with increased expression of the BMP-15 mRNA, are considered markers of a higher probability of blastocyst development on day 5 (28). Alfaidy, et al identified PROK1 expression levels in individual FF samples as a predictor the in vitro fertilization (IVF) outcomes (29). Moreover, the expression of some non-coding RNAs, such as miR-451, in FF samples was positively correlated with the quality of blastocyst-stage embryos obtained from patients with endometriosis (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Canosa, et al, reduced levels of Cx43 expression in the cumulus cells, coupled with increased expression of the BMP-15 mRNA, are considered markers of a higher probability of blastocyst development on day 5 (28). Alfaidy, et al identified PROK1 expression levels in individual FF samples as a predictor the in vitro fertilization (IVF) outcomes (29). Moreover, the expression of some non-coding RNAs, such as miR-451, in FF samples was positively correlated with the quality of blastocyst-stage embryos obtained from patients with endometriosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Alfaidy, et al. identified PROK1 expression levels in individual FF samples as a predictor the in vitro fertilization (IVF) outcomes ( 29 ). Moreover, the expression of some non-coding RNAs, such as miR-451, in FF samples was positively correlated with the quality of blastocyst-stage embryos obtained from patients with endometriosis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, concentration of PROK1 protein in the follicular fluid is relevant to the follicular size and is predictive of the oocyte competence 21 . Follicle Stimulating Hormone and hCG up-regulated PROK1 protein secretion in cumulus cell primary cultures, probably through the cAMP pathway 21 . Successful embryo implantation may be predicted by PROK1 concentration in the follicular fluid and fertilization culture media in conventional in vitro fertilization-embryo transfer 22 .…”
Section: Biological Functions Of the Prokineticin1mentioning
confidence: 99%
“…Similarly, transgenic mice overexpressing PKR2 in their cardiomyocytes (TG-PKR2) showed hypertrophy and impaired endothelial integrity related to paracrine regulation ( Urayama et al, 2009 ). Overall, pressure overload-mediated maintenance of PKR2 signaling in cardiomyocytes contributes to cardiac hypertrophy via autocrine signaling and to vascular rarefaction via cardiac cytokine-mediated communication between cardiomyocytes and ECs ( Guilini et al, 2010 ; Alfaidy et al, 2019 ). In ECs cultured in vitro, activation of PKR2, unlike PKR1, does not induce angiogenesis but couples to G α 12-13-mediated degradation of zonula occludens one, a cell-cell adhesion molecule, at tight junctions and forms a fenestration of ECs.…”
Section: Role Of the Prokineticins In Cardiovascular Diseasesmentioning
confidence: 99%
“…PK1 and PK2 signaling have been reported to be associated with physiologic and pathologic aspects of the reproductive system ( Ferrara et al, 2004 ; Brouillet et al, 2010 , 2012a, b , 2013 ; Dunand et al, 2014 ; Alfaidy, 2016 ; Alfaidy et al, 2019 ). PK2 directly controls the migration of GnRH neurons, which affects the development of the female and male reproductive organs ( Dodé et al, 2006 ; Dodé and Rondard, 2013 ), while PK1 mainly controls female reproductive functions, especially those associated with pregnancy.…”
Section: Role Of Prokineticin System In Reproductive System Functions...mentioning
confidence: 99%